Modernizing Democracy: Innovations in Citizen Participation - Buss, Terry F; Redburn, F. Stevens; Guo, Kristina (Transformational trends in governance and democracy, 2006)
Intended for public administration professionals, scholars, and students interested in citizen participation. This work brings together analyses of innovative practices, from hands-on community learning and focus groups to high-tech information systems and decision support technologies.